The Language Arts syllabus 1975: Comment and counter comment - Carrington, Lawrence D.; Borely, C. B. (Faculty of Education, UWI St. Augustine, Trinidad, 1978)
Very soon after the appearance of the New Primary School Syllabus in Trinidad and Tobago, a number of letters appeared in the press commenting adversely on the section dealing with the teaching of Language Arts. Because so much of the commentary was considered ill-informed and misguided, the authors wrote a series of eight letters in the Sunday Guardian newspaper in which they sought to correct the wrong impression apparent in the letters. This document contains the complete set of relevant items with some modifications and expansion of the original articles to answer queries raised by several persons.
Keywords: language education